Linguistic Microaggressions in Indigenous Educational Community Environments: A Pragmatic Study of Language Use - Nuzmi Sasferi (Newinera Publisher, 2026)
Linguistic microaggression is a subtle form of discriminatory communication that frequently occurs in multicultural educational interactions and may affect social relationships, cultural identity, and language practices within indigenous communities. This study aimed to examine the forms and levels of linguistic microaggression in indigenous community environments and to analyze the relationship between indigenous educational environments and pragmatic language politeness. An explanatory sequential mixed methods design was employed. Quantitative data were collected from 30 participants representing native-speaking communities, religious education communities, and migrant communities in Kerinci and Sungai Penuh through a structured questionnaire. The data were analyzed using descriptive statistics, the Kruskal–Wallis test, and Spearman rank correlation. Qualitative data were obtained through in-depth interviews, conversational observations, and naturalistic recordings and analyzed using thematic analysis. The quantitative findings revealed significant differences in pragmatic language politeness among the three community groups (χ² = 29.000, p < 0.001). A strong positive relationship was found between intercultural and ethnolinguistic engagement and pragmatic language politeness (ρ = 0.866, p < 0.001), while linguistic microaggression dimensions showed moderate negative correlations with pragmatic language politeness (ρ = −0.500, p < 0.05). Qualitative findings identified recurring patterns of microinsult, microinvalidation, and microassault, alongside mitigation, face-saving, and intercultural adaptation strategies used to maintain social harmony. The study concludes that linguistic microaggression is closely associated with sociocultural values, identity negotiation, and power relations, while indigenous education contributes to the development of pragmatic sensitivity and culturally respectful communication.